Preparation method of MTO catalyst
By modifying the silicon aluminum phosphate molecular sieve and combining it with ceramic fibers and other materials, an MTO catalyst with high wear resistance and high selectivity was prepared, which solved the problems of poor wear resistance and low selectivity of the catalyst in the prior art, and achieved an efficient methanol-to-olefin reaction.
Patent Information
- Application Number
- CN202311227503.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-21
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2043-09-21
AI Technical Summary
In the prior art, there are problems such as poor wear resistance strength of the molecular sieve fluidized bed catalyst and low selectivity of ethylene and propylene.
By treating the silica-aluminum phosphate molecular sieve in an alcohol solution containing titanate and mixing it with ceramic fibers, binder and matrix material, forming a suspension, high-speed shearing, spray-drying and calcining, an MTO catalyst with high wear resistance and high selectivity was prepared.
The catalyst's high wear resistance and high selectivity of ethylene and propylene are achieved, which reduces the wear index and ensures the rationality of catalytic performance and production costs.
Smart Images

Figure CN119680634A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of catalyst preparation, and in particular to a method for preparing a MTO catalyst. Background Art
[0002] Methanol-To-Olefin (MTO) refers to the process technology of using methanol, which is usually produced from natural gas or coal, to produce low-carbon olefins such as polymerization-grade ethylene and propylene under the action of a catalyst. The methanol-to-olefin route has attracted widespread attention because its raw materials can be obtained from synthesis gas in large quantities, cheaply and conveniently. In recent years, dozens of methanol-to-olefin (MTO) units have been put into commercial operation, and have achieved very good economic and social benefits.
[0003] The core of methanol to olefins technology is the development of molecular sieve catalysts. In the early stage, the catalysts used in methanol to olefins were mostly silica-alumina zeolite molecular sieves, such as ZSM-5, but their pore size was relatively large, the acidity was too strong, and the yield of low-carbon olefins was not high. In 1982, the United Carbide Corporation (UCC) of the United States synthesized the SAPO series of silica-alumina phosphate molecular sieves for the first time. The most eye-catching one is SAPO-34 molecular sieve, which has a chabazite-like structure, a small pore size, moderate acidity and strong hydrothermal stability. It shows excellent selectivity for low-carbon olefins in the catalytic methanol to low-carbon olefin reaction, which has attracted widespread attention from Chinese and foreign researchers.
[0004] When molecular sieves are used in industrial catalysis, it is generally not possible to use 100% of the molecular sieves to prepare catalysts for industrial processes. First, the molecular sieves themselves have poor adhesion and the particles are too fine, making them difficult to form into catalysts that can be directly used in industrial processes. Second, the manufacturing cost of molecular sieves is generally high. If 100% of the molecular sieves are used as industrial catalysts, the cost will increase. Since most MTO processes use fluidized bed reactors, the existing technology generally prepares the molecular sieves directly with binders, liquid media, etc. into a suspension, and then makes a microsphere fluidized bed catalyst by shearing, drying and roasting.
[0005] In summary, although some existing patents involve the issue of improving the wear resistance of fluidized bed catalysts, the wear resistance of fluidized bed catalysts still needs to be further improved, while also taking into account that the catalytic performance of the catalyst does not decrease and the production energy consumption does not increase. Summary of the invention
[0006] The technical problem to be solved by the present invention is that the molecular sieve fluidized bed catalyst in the prior art has poor wear resistance and low selectivity for ethylene and propylene, and a method for preparing an MTO catalyst is provided. The catalyst prepared by the method has the characteristics of high wear resistance and good selectivity for ethylene and propylene.
[0007] The first aspect of the present invention provides a method for preparing an MTO catalyst, comprising:
[0008] a) treating the silicoaluminophosphate molecular sieve in an alcohol solution containing titanate, and drying to obtain a modified molecular sieve;
[0009] b) mixing the modified molecular sieve obtained in step a), a liquid medium, a matrix material, a structural reinforcement material and a binder to form a suspension; the structural reinforcement material is a ceramic fiber with a diameter of 2 to 6 μm and an aspect ratio of 1 to 15;
[0010] c) high-speed shearing the suspension obtained in step b) and spray drying to obtain a microsphere catalyst;
[0011] d) calcining the microsphere catalyst obtained in step c) to obtain the catalyst.
[0012] According to one aspect of the present invention, the treatment method in step a) is to mix and stir the molecular sieve and the alcohol solution containing the titanate in a certain weight ratio and then treat. The weight ratio of the molecular sieve to the alcohol solution containing the titanate is 10 to 40:100, preferably 10 to 30:100, the treatment temperature is 30 to 90°C, preferably 50 to 90°C, and the treatment time is 30 to 90 minutes, preferably 30 to 50 minutes.
[0013] According to one aspect of the present invention, after the treatment in step a), conventional filtering and washing operations are first performed and then drying is performed. The drying conditions are: temperature of 80-130° C. and time of 0.5-12 hours.
[0014] According to one aspect of the present invention, the molecular sieve in step a) is washed with water and then solid-liquid separated before being treated with the alcohol solution containing titanate, and the obtained solid is not dried.
[0015] According to one aspect of the present invention, deionized water is added to the alcohol solution containing titanate, and the weight ratio of titanate, alcohol and water satisfies the following ratio: titanate:alcohol=1-4:100, deionized water:alcohol=1-5:100.
[0016] According to one aspect of the present invention, the titanate is selected from at least one of tetrabutyl titanate and tetraisopropyl titanate, preferably tetrabutyl titanate (purity ≥ 98 wt %).
[0017] According to one aspect of the present invention, the alcohol is selected from at least one of ethanol and isopropanol, preferably ethanol.
[0018] According to one aspect of the present invention, the silicoaluminophosphate molecular sieve is selected from at least one of SAPO-18 and SAPO-34, preferably SAPO-34; the Si / Al molar ratio of the SAPO-34 molecular sieve is 0.05-0.5:1, and the Si / Al molar ratio of the SPAO-18 molecular sieve is 0.1-0.3.
[0019] According to one aspect of the present invention, the structural reinforcement material is ceramic fiber, which is an ultra-fine fiber made by spinning a mixture of electro-fused alumina and silica, wherein the mass content of Al2O3+SiO2 is ≥98.0%.
[0020] According to one aspect of the present invention, the ceramic fiber needs to be pretreated in a 0.1-0.3 mol / L phosphoric acid solution for 0.5-2.0 hours. The weight ratio of the ceramic fiber to the phosphoric acid solution is 20-60:100, the pretreatment is carried out under stirring, and the pretreatment temperature is 20-30°C. After the pretreatment, conventional filtration, washing, and drying are performed to obtain the pretreated ceramic fiber.
[0021] According to one aspect of the present invention, the solid content of the suspension in step b) is preferably 20-50%, and the pH value is preferably 2.5-5.5.
[0022] According to one aspect of the present invention, in step b), the binder is a sol, the matrix material is clay and / or hydrotalcite, and the liquid medium is deionized water.
[0023] According to one aspect of the present invention, the binder in step b) is preferably silica sol or alumina sol; the matrix material is clay and / or hydrotalcite, preferably at least one selected from kaolin, bentonite and hydrotalcite, more preferably kaolin.
[0024] According to one aspect of the present invention, in the suspension of step b), calculated by weight ratio: the molecular sieve is preferably 5-40 weight %; the binder is preferably 1-20 weight %; the matrix material is preferably 5-50 weight %; the liquid medium is preferably 10-88 weight %; and the structural reinforcement material is preferably 1-10 weight %.
[0025] According to one aspect of the present invention, in the suspension of step b), calculated by weight ratio: the molecular sieve is more preferably 10-30 weight %; the binder is more preferably 1-10 weight %; the matrix material is more preferably 10-40 weight %; the liquid medium is more preferably 15-77 weight %; and the structural reinforcement material is more preferably 2-8 weight %.
[0026] According to one aspect of the present invention, in step c), the high-speed shearing is performed until 90% of the particles in the mixed liquid have a size of less than 5 microns.
[0027] According to one aspect of the present invention, the conditions for spray drying in step c) are: inlet temperature of 180-300° C., outlet temperature of 100-160° C., and centrifugal speed of 5000-15000 rpm.
[0028] According to one aspect of the present invention, in step d), the calcination temperature is 500-900°C, preferably 550-750°C, the calcination time is 0.5-24 hours, preferably 4-12 hours, and the calcination atmosphere is a flowing atmosphere, preferably flowing air, and the flow power comes from the negative pressure.
[0029] According to one aspect of the present invention, the catalyst prepared by spray drying has a wear index of less than 1.00 wt% / h after high-temperature calcination, preferably a wear index of less than 0.50 wt% / h, more preferably a wear index of less than 0.30 wt% / h, and more preferably a wear index of 0.16-0.19 wt% / h.
[0030] According to one aspect of the present invention, the average particle size of the catalyst prepared in step d) is 70-130 microns, preferably 80-100 microns.
[0031] According to one aspect of the present invention, in the catalyst prepared in step d), the content of TiO2 calculated as Ti is 0.500%-1.500% based on the weight of the catalyst.
[0032] Compared with the prior art, the present invention has the following beneficial effects:
[0033] 1. The MTO catalyst of the present invention has high catalytic performance and low wear index, and is applied to the methanol to olefin reaction, and has the characteristics of high selectivity for low-carbon olefins and low wear index. Under the premise of ensuring the catalytic performance of the MTO fluidized bed catalyst, the production cost of the catalyst is not significantly increased, and a fluidized bed catalyst with high wear resistance is obtained.
[0034] 2. The grain size of the silicoaluminophosphate molecular sieve prepared by the hydrothermal synthesis method of the prior art is only a few hundred nanometers. During the drying process of the molecular sieve raw powder, the molecular sieve grains with high surface energy are very likely to agglomerate. The agglomerated molecular sieve grains in the spray-formed catalyst microspheres will reduce the wear resistance of the catalyst due to the local stress difference caused by the uneven distribution between the molecular sieve and the matrix material. In the present invention, before the silicoaluminophosphate molecular sieve is dried, the surface of the molecular sieve is modified with tetrabutyl titanate, and the modified molecular sieve is not easy to agglomerate. At the same time, ceramic fibers are added in the pulping process of the catalyst spray drying, which can not only obtain a more uniform slurry, but also the ceramic short fibers are distributed in the spherical structure sintered by the molecular sieve, kaolin and aluminum sol, which plays a role in strengthening the structure, thereby obtaining a silicoaluminophosphate fluidized bed catalyst with a low wear index. In addition, TiO2 generated after calcination of titanate located on the surface of molecular sieve grains can reduce the micro stress between the molecular sieve grains and the matrix material and improve the grain boundary bonding strength, which is one of the reasons why the catalyst prepared by the present invention has higher wear resistance. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] Figure 1 This is the XRD spectrum of the SAPO-34 molecular sieve obtained in Preparation Example 5;
[0036] Figure 2 This is the XRD spectrum of the SAPO-18 molecular sieve obtained in Example 9;
[0037] Figure 3 This is a SEM photo of the internal structure of the molecular sieve fluidized bed catalyst obtained in Comparative Example 1 after grinding and crushing;
[0038] Figure 4 This is a SEM photo of the internal structure of the molecular sieve fluidized bed catalyst obtained in Example 1 after grinding and crushing;
[0039] Figure 5 This is a SEM photograph of the molecular sieve fluidized bed catalyst obtained in Example 1. DETAILED DESCRIPTION
[0040] The wear index of the present invention is measured on a D5757-11 fluidized bed abrasion tester of VINCI Company, and is measured using the method of Chapter 7 of Q / SH 361.552-2017.
[0041] In the present invention, the wear index ω , the value is expressed as mass fraction per hour (% / h) and is calculated according to the following formula:
[0042]
[0043] Where:
[0044] m5——the mass of the powder collection system after 5 hours, in grams (g);
[0045] m1——the mass of the powder collection system after 1 hour, in grams (g);
[0046] m——the numerical value of the sample mass, in grams (g);
[0047] m0——the mass of the powder collection system before the test, in grams (g);
[0048] 4——The unit is h.
[0049] The arithmetic mean of the two determination results is taken as the analysis result and rounded off according to the provisions of GB / T 8170 to an accuracy of 0.01% / h.
[0050] The average particle size of the catalyst of the present invention is measured by a laser particle size analyzer (model: Malvern 2000).
[0051] The present invention has no particular limitation on the high-speed shearing, which can be performed according to conventional technical means in the art, and the present invention will not elaborate on it here.
[0052] The morphology of the catalyst of the present invention is measured using a Philips XL300 scanning electron microscope.
[0053] The internal structure of the catalyst of the present invention is measured using a Philips XL300 scanning electron microscope, and the catalyst is ground into pieces to observe the internal structure.
[0054] The Ti content in the catalyst of the present invention is tested by ICP, instrument parameters: Varian 725ES, test method: standard curve method. Test conditions are shown in Table 1:
[0055] Table 1
[0056] name Technical Parameters name Technical Parameters Plasma power 1100W Injection time 45s Plasma gas (Ar) <![CDATA[15L min -1 ]]> Reading time 5s Auxiliary gas (Ar) <![CDATA[1.5L min -1 ]]> Injection pump speed 15rpm Nebulizer flow rate <![CDATA[0.75L min -1 ]]> Observation Mode Radial Observation height 10mm Ti measurement wavelength 336.122nm
[0057] The present invention will be described in detail below through examples.
[0058] The reagents in the following examples are commercially available and of analytical grade.
[0059] [Preparation Example 1]
[0060] This preparation example is used to illustrate the preparation of the tetrabutyl titanate ethanol solution of the present invention:
[0061] Weigh 100 parts of ethanol solution and 4 parts of tetrabutyl titanate by weight, add the tetrabutyl titanate dropwise into the ethanol solution under stirring, weigh 5 parts of deionized water, add into the above solution and continue stirring until it is uniform.
[0062] [Preparation Example 2]
[0063] This preparation example is used to illustrate the preparation of the tetrabutyl titanate ethanol solution of the present invention:
[0064] Weigh 100 parts of ethanol solution and 1 part of tetrabutyl titanate by weight, add the tetrabutyl titanate dropwise into the ethanol solution under stirring, weigh 2 parts of deionized water, add into the above solution and continue stirring until it is uniform.
[0065] [Preparation Example 3]
[0066] This preparation example is used to illustrate the preparation of the tetrabutyl titanate ethanol solution of the present invention:
[0067] Weigh 100 parts of ethanol solution and 2 parts of tetrabutyl titanate by weight, add the tetrabutyl titanate dropwise into the ethanol solution under stirring, weigh 3 parts of deionized water, add into the above solution and continue stirring until it is uniform.
[0068] [Preparation Example 4]
[0069] This preparation example is used to illustrate the preparation of the isopropyl titanate isopropanol solution of the present invention:
[0070] Weigh 100 parts of ethanol solution and 2 parts of isopropyl titanate by weight, add isopropyl titanate dropwise into the isopropyl alcohol solution under stirring, weigh 3 parts of deionized water, add into the above solution and continue stirring until it is uniform.
[0071] [Preparation Example 5]
[0072] This preparation example is used to illustrate the preparation of the SAPO-34 molecular sieve described in the present invention:
[0073] 12.0 parts of γ-Al2O3 and 35.0 parts of deionized water were weighed and mixed evenly to form a solution a; 23.1 parts of phosphoric acid (85 weight %) and 37.5 parts of deionized water were mixed evenly to form a solution b; a and b were mixed and stirred at room temperature for 2 hours to form a uniform solution c; while maintaining stirring, 20.2 parts of triethylamine, 15 parts of tetraethylammonium hydroxide TEAOH, 4.5 parts of silica sol (40 weight %) and 10.0 parts of deionized water were added to c in sequence, and mixture A was obtained after sufficient stirring.
[0074] Mixture A was placed in a crystallization kettle and heated to 200°C under stirring. After crystallization for 24 hours, the solid product was recovered by solid-liquid separation. The solid product was washed three times with deionized water and then dried. XRD characterization showed that the obtained product was pure phase SAPO-34 (Si / Al molar ratio was 0.15).
[0075] [Preparation Example 6]
[0076] This preparation example is used to illustrate the pretreatment preparation of the ceramic fiber of the present invention:
[0077] Weigh 1 part of ceramic fiber cotton (diameter 5 μm, aspect ratio 1.2-6) and 5 parts of 0.1 mol / L phosphoric acid solution, stir at 25° C. for 1.0 hour, filter, wash and dry to obtain pretreated ceramic fiber.
[0078] [Preparation Example 7]
[0079] This preparation example is used to illustrate the pretreatment preparation of the ceramic fiber of the present invention:
[0080] Weigh 1 part of ceramic fiber cotton (diameter 4 μm, aspect ratio 1.5-7) and 5 parts of 0.1 mol / L phosphoric acid solution, stir at 25° C. for 2.0 hours, filter, wash and dry to obtain pretreated ceramic fiber.
[0081] Preparation Example 88
[0082] This preparation example is used to illustrate the pretreatment preparation of the ceramic fiber of the present invention:
[0083] Weigh 1 part of ceramic fiber cotton (diameter 2 μm, aspect ratio 4-15) and 3 parts of 0.2 mol / L phosphoric acid solution, stir at 25° C. for 0.5 hour, filter, wash and dry to obtain pretreated ceramic fiber.
[0084] [Example 1]
[0085] The SAPO-34 molecular sieve prepared by hydrothermal synthesis in Preparation Example 5 was separated from the solid and liquid. The obtained solid product was washed with deionized water for 3 times and then added to the tetrabutyl titanate ethanol solution obtained in Preparation Example 1 at a weight ratio of 20:100 without drying. The mixture was stirred at 60°C for 30 minutes, and the solution was filtered out. The obtained solid was washed once with an ethanol solution to remove free tetrabutyl titanate and dried at 110°C for 6 hours to obtain a titanate-modified SAPO-34 molecular sieve.
[0086] The raw materials are weighed according to the ratio of 16% (weight) of the modified SAPO-34 molecular sieve; 18% (weight) of kaolin; 4% (weight) of aluminum sol; 2% (weight) of the ceramic fiber obtained in Preparation Example 6; and 60% (weight) of deionized water. Except for water, the raw material ratios here are all dry weight ratios. First, the modified SAPO-34 molecular sieve and a certain amount of water are mixed, stirred for 1 hour, and high-speed sheared for 15 minutes to form a uniform molecular sieve suspension; aluminum sol is added to the suspension, stirred rapidly for 15 minutes, and then high-speed sheared for 15 minutes; kaolin is added, stirred for 30 minutes, ceramic fiber slurry is added, stirred for 15 minutes, and then high-speed sheared for 45 minutes to obtain a suspension, the solid content of the suspension is 40%, and the pH value of the suspension is 2.9. 90% of the particles in this suspension are less than 3.6 microns. The suspension was spray dried (inlet temperature was 290° C., outlet temperature was 140° C., and centrifugal speed was 10,000 rpm), and then calcined at 600° C. for 6 h under air conditions to obtain a molecular sieve fluidized bed catalyst.
[0087] The average particle size and TiO2 content of the catalyst obtained in Example 1 are shown in Table 2.
[0088] [Example 2]
[0089] The SAPO-34 molecular sieve prepared by hydrothermal synthesis in Preparation Example 5 was separated from the solid and liquid. The obtained solid product was washed with deionized water for 3 times and then added to the tetrabutyl titanate ethanol solution obtained in Preparation Example 1 at a weight ratio of 20:100 without drying. The mixture was stirred at 30°C for 30 minutes, and the solution was filtered out. The obtained solid was washed once with an ethanol solution to remove free tetrabutyl titanate and dried at 110°C for 6 hours to obtain a titanate-modified SAPO-34 molecular sieve.
[0090] The raw materials are weighed according to the ratio of 16 wt% of the above modified SAPO-34 molecular sieve; 17 wt% kaolin; 3 wt% aluminum sol; 4 wt% ceramic fiber obtained in Preparation Example 6; 60 wt% deionized water. Except for water, the raw material ratios here are all dry weight ratios. First, the above modified SAPO-34 molecular sieve is mixed with a certain amount of water, stirred for 1 hour, and high-speed sheared for 15 minutes to form a uniform molecular sieve suspension; aluminum sol is added to the suspension, stirred rapidly for 15 minutes, and then high-speed sheared for 15 minutes; kaolin is added, stirred for 30 minutes, ceramic fiber slurry is added, stirred for 15 minutes, and then high-speed sheared for 45 minutes to obtain a suspension, the solid content of the suspension is 39.8%, and the pH value of the suspension is 3.2. 90% of the particles in this suspension are less than 3.8 microns. Spray drying (same as Example 1), then calcined at 600°C under air conditions for 6 hours to obtain a molecular sieve fluidized bed catalyst.
[0091] The average particle size and TiO2 content of the catalyst obtained in Example 2 are shown in Table 2.
[0092] [Example 3]
[0093] The SAPO-34 molecular sieve prepared by hydrothermal synthesis in Preparation Example 5 was separated from the solid and liquid. The obtained solid product was washed with deionized water for 3 times and then added to the tetrabutyl titanate ethanol solution obtained in Preparation Example 1 at a weight ratio of 20:100 without drying. The mixture was stirred at 90°C for 30 minutes, and the solution was filtered out. The obtained solid was washed once with an ethanol solution to remove free tetrabutyl titanate and dried at 110°C for 6 hours to obtain a titanate-modified SAPO-34 molecular sieve.
[0094] The raw materials are weighed according to the ratio of 16 wt% of the modified SAPO-34 molecular sieve; 15 wt% of kaolin; 3 wt% of aluminum sol; 6 wt% of the ceramic fiber obtained in Preparation Example 6; and 60 wt% of deionized water. Except for water, the raw material ratios here are all dry weight ratios. First, the modified SAPO-34 molecular sieve is mixed with a certain amount of water, stirred for 1 hour, and high-speed sheared for 15 minutes to form a uniform molecular sieve suspension; aluminum sol is added to the suspension, stirred rapidly for 15 minutes, and then high-speed sheared for 15 minutes; kaolin is added, stirred for 30 minutes, ceramic fiber slurry is added, stirred for 15 minutes, and then high-speed sheared for 45 minutes to obtain a suspension, the solid content of the suspension is 40%, and the pH value of the suspension is 3.0. 90% of the particles in this suspension are less than 3.8 microns. Spray drying (same as Example 1), then calcined at 600°C under air conditions for 6 hours to obtain a molecular sieve fluidized bed catalyst.
[0095] The average particle size and TiO2 content of the catalyst obtained in Example 3 are shown in Table 2.
[0096] [Example 4]
[0097] The SAPO-34 molecular sieve prepared by hydrothermal synthesis in Preparation Example 5 was separated from the solid and liquid. The obtained solid product was washed with deionized water for 3 times and then added to the tetrabutyl titanate ethanol solution obtained in Preparation Example 1 at a weight ratio of 40:100 without drying. The mixture was stirred at 90°C for 30 minutes, and the solution was filtered out. The obtained solid was washed once with an ethanol solution to remove free tetrabutyl titanate and dried at 110°C for 8 hours to obtain a titanate-modified SAPO-34 molecular sieve.
[0098] The raw materials were weighed according to the ratio of 14 wt% of the modified SAPO-34 molecular sieve; 18 wt% of kaolin; 4 wt% of aluminum sol; 4 wt% of the ceramic fiber obtained in Preparation Example 7; and 60 wt% of deionized water. Except for water, the raw material ratios here are all dry weight ratios. The rest are the same as in Example 1.
[0099] The average particle size and TiO2 content of the catalyst obtained in Example 4 are shown in Table 2.
[0100] [Example 5]
[0101] The SAPO-34 molecular sieve prepared by hydrothermal synthesis in Preparation Example 5 was separated from the solid and liquid. The obtained solid product was washed with deionized water for 3 times and then added to the tetrabutyl titanate ethanol solution obtained in Preparation Example 2 at a weight ratio of 15:100 without drying. The mixture was stirred at 90°C for 60 minutes, and the solution was filtered out. The obtained solid was washed once with ethanol solution to remove free tetrabutyl titanate and dried at 110°C for 8 hours to obtain the titanate-modified SAPO-34 molecular sieve.
[0102] Raw materials were weighed according to the ratio of 16 wt % of the modified SAPO-34 molecular sieve; 18 wt % of kaolin; 4 wt % of aluminum sol; 2 wt % of the ceramic fiber obtained in Preparation Example 7; and 60 wt % of deionized water. Except for water, the raw material ratios here are all dry weight ratios. Others are the same as in Example 1.
[0103] The average particle size and TiO2 content of the catalyst obtained in Example 5 are shown in Table 2.
[0104] [Example 6]
[0105] The SAPO-34 molecular sieve prepared by hydrothermal synthesis in Preparation Example 5 was separated from the solid and liquid. The obtained solid product was washed three times with deionized water and then added to the tetrabutyl titanate ethanol solution obtained in Preparation Example 2 at a weight ratio of 10:100 without drying. The mixture was stirred at 60°C for 45 minutes, and the solution was filtered out. The obtained solid was washed once with an ethanol solution to remove free tetrabutyl titanate and dried at 110°C for 8 hours to obtain a titanate-modified SAPO-34 molecular sieve.
[0106] Raw materials were weighed according to the ratio of 15 wt% of the modified SAPO-34 molecular sieve; 14 wt% of kaolin; 3 wt% of aluminum sol; 8 wt% of the ceramic fiber obtained in Preparation Example 8; and 60 wt% of deionized water. Except for water, the raw material ratios here are all dry weight ratios. Others are the same as in Example 1.
[0107] The average particle size and TiO2 content of the catalyst obtained in Example 6 are shown in Table 2.
[0108] [Example 7]
[0109] The SAPO-34 molecular sieve prepared by hydrothermal synthesis in Preparation Example 5 was separated from the solid and liquid. The obtained solid product was washed with deionized water for 3 times and then added to the tetrabutyl titanate ethanol solution obtained in Preparation Example 3 at a weight ratio of 30:100 without drying. The mixture was stirred at 70°C for 45 minutes, and the solution was filtered out. The obtained solid was washed once with an ethanol solution to remove free tetrabutyl titanate and dried at 110°C for 6 hours to obtain a titanate-modified SAPO-34 molecular sieve.
[0110] The raw materials were weighed according to the ratio of 16 wt % of the modified SAPO-34 molecular sieve; 18 wt % of kaolin; 4 wt % of aluminum sol; 2 wt % of the ceramic fiber obtained in Preparation Example 8; and 60 wt % of deionized water. Except for water, the raw material ratios here are all dry weight ratios. The rest are the same as in Example 1.
[0111] The average particle size and TiO2 content of the catalyst obtained in Example 7 are shown in Table 2.
[0112] [Example 8]
[0113] Compared with Example 1, the only difference is that the tetrabutyl titanate ethanol solution in Preparation Example 1 is replaced by the tetraisopropyl titanate isopropanol solution in Preparation Example 4.
[0114] The average particle size and TiO2 content of the catalyst obtained in Example 8 are shown in Table 2.
[0115] [Example 9]
[0116] Compared with Example 1, the only difference is that the SAPO-34 molecular sieve is replaced by a SAPO-18 molecular sieve (Si / Al molar ratio is 0.15).
[0117] The average particle size and TiO2 content of the catalyst obtained in Example 9 are shown in Table 2.
[0118] [Example 10]
[0119] Compared with Example 1, the only difference is that the ceramic fibers are not pretreated.
[0120] The average particle size and TiO2 content of the catalyst obtained in Example 10 are shown in Table 2.
[0121] (Comparative Example 1)
[0122] Compared with Example 1, the only difference is that the pure-phase SAPO-34 molecular sieve of Preparation Example 5 is used, and no ceramic fiber is added to the suspension.
[0123] Weigh the raw materials according to the ratio of 16% (weight) SAPO-34 molecular sieve; 20% (weight) kaolin; 4% (weight) aluminum sol; 60% (weight) deionized water. Except for water, the raw material ratios here are all dry weight ratios. First, mix the SAPO-34 molecular sieve with a certain amount of water, stir for 1 hour, and then high-speed shear for 15 minutes; add aluminum sol, stir quickly for 15 minutes, and high-speed shear for 15 minutes; add kaolin, stir for 30 minutes, and then high-speed shear mixing for 45 minutes to obtain a suspension, the solid mass content of the suspension is 38%, and the pH value of the suspension is 4.2. It is determined that 90% of the particle size in this suspension is less than 3.9 microns. The suspension is spray-dried (same as Example 1), and then calcined at 600°C for 6 hours under air conditions to obtain a molecular sieve fluidized bed catalyst.
[0124] The average particle size and TiO2 content of the catalyst obtained in Comparative Example 1 are shown in Table 2.
[0125] [Comparative Example 2]
[0126] Compared with Comparative Example 1, the only difference is that: the total dry basis weight in the spray slurry of Comparative Example 1 is regarded as 100 parts, 6 parts of tetrabutyl titanate are additionally added, and the re-prepared slurry is spray-dried and calcined to obtain a silicoaluminophosphate molecular sieve fluidized bed catalyst.
[0127] The average particle size and TiO2 content of the catalyst obtained in Comparative Example 2 are shown in Table 2.
[0128] [Comparative Example 3]
[0129] Compared with Example 1, the only difference is that the pure phase SAPO-34 molecular sieve of Preparation Example 5 is used.
[0130] The average particle size and TiO2 content of the catalyst obtained in Comparative Example 3 are shown in Table 2.
[0131] [Test Example 1]
[0132] The fluidized bed catalysts obtained in Examples 1-10 and Comparative Examples 1-3 were respectively tested for wear index using a D5757-11 fluidized bed abrasion tester. The results are shown in Table 3.
[0133] [Test Example 2]
[0134] The silicoaluminophosphate molecular sieve catalysts obtained in Examples 1-10 and Comparative Examples 1-3 were respectively used for methanol to olefin reaction on a small fixed fluidized bed. The reaction conditions were: 40 g catalyst, pure methanol feed, mass space velocity (WHSV) 4 h- 1 , reaction temperature 480°C, reaction pressure normal pressure. The reaction results are shown in Table 3.
[0135] Table 2
[0136] Ti content (wt%) Average particle size of catalyst (micrometers) Example 1 0.829 85 Example 2 0.801 85 Example 3 0.897 86 Example 4 0.799 84 Example 5 0.787 88 Example 6 0.932 87 Example 7 0.865 86 Example 8 0.804 85 Example 9 0.825 86 Example 10 0.812 87 Comparative Example 1 0.021 88 Comparative Example 2 0.847 84 Comparative Example 3 0.022 86
[0137] Table 3
[0138]
[0139] The above describes the specific implementation of the present invention in detail, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the various technical features being combined in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A method for preparing an MTO catalyst, comprising: a) treating the silicoaluminophosphate molecular sieve in an alcohol solution containing titanate, and drying to obtain a modified molecular sieve; b) mixing the modified molecular sieve obtained in step a), a liquid medium, a matrix material, a structural reinforcement material and a binder to form a suspension; the structural reinforcement material is a ceramic fiber with a diameter of 2 to 6 μm and an aspect ratio of 1 to 15; c) high-speed shearing the suspension obtained in step b) and spray drying to obtain a microsphere catalyst; d) calcining the microsphere catalyst obtained in step c) to obtain the catalyst.
2. The preparation method according to claim 1, characterized in that: The treatment method in step a) is to mix and stir the silicoaluminophosphate molecular sieve and the alcohol solution containing titanate in a certain weight ratio and then treat them. The weight ratio of the molecular sieve to the alcohol solution containing titanate is 10-40:100, preferably 10-30:100, the treatment temperature is 30-90°C, preferably 50-90°C, and the treatment time is 30-90 minutes, preferably 30-50 minutes.
3. The preparation method according to claim 2, characterized in that: The silicoaluminophosphate molecular sieve prepared in step a) is washed with water and then subjected to solid-liquid separation before being treated with the titanate ethanol solution, and the obtained solid is not dried.
4. The preparation method according to claim 1 or 2, characterized in that: Deionized water is added to the alcohol solution containing titanate, and the weight ratio of titanate, alcohol and water satisfies the following ratio: titanate:alcohol=1-4:100, and deionized water:alcohol=1-5:
100.
5. The preparation method according to claim 1, characterized in that: The titanate is selected from at least one of tetrabutyl titanate and tetraisopropyl titanate, preferably tetrabutyl titanate; the alcohol is selected from at least one of ethanol and isopropanol, preferably ethanol; the silicoaluminophosphate molecular sieve is selected from at least one of SPAO-34 and SPAO-18, preferably SAPO-34 molecular sieve; the Si / Al molar ratio of the SAPO-34 molecular sieve is 0.05-0.5:1, and the Si / Al molar ratio of the SPAO-18 molecular sieve is 0.1-0.
3.
6. The preparation method according to claim 1, characterized in that: The ceramic fiber is pretreated in a 0.1-0.3 mol / L phosphoric acid solution for 0.5-2.0 hours at a pretreatment temperature of 20-30° C.; and / or the weight ratio of the ceramic fiber to the phosphoric acid solution is 20-60:
100.
7. The preparation method according to claim 1, characterized in that: In the suspension of step b), calculated by weight ratio: the molecular sieve is 5-40% by weight, preferably 10-30% by weight; the binder is 1-20% by weight, preferably 1-10% by weight; the matrix material is 5-50% by weight, preferably 10-40% by weight; the liquid medium is 10-88% by weight, preferably 15-77% by weight; the structural reinforcement material is 1-10% by weight, preferably 2-8% by weight.
8. The preparation method according to claim 1 or 7, characterized in that: Step b) the solid content of the suspension is 20-50% by weight and the pH value is 2.5-5.5; And / or, in step c), high-speed shearing is performed until 90% of the particles in the mixed liquid have a size of less than 5 microns.
9. The preparation method according to claim 1, characterized in that: Step b) The binder is a sol, preferably a silica sol or an alumina sol; the matrix material is clay and / or hydrotalcite, preferably at least one selected from kaolin, bentonite and hydrotalcite, more preferably kaolin; and the liquid medium is deionized water.
10. The preparation method according to claim 1, characterized in that: In step d), the calcination temperature is 500-900° C., preferably 550-750° C., the calcination time is 0.5-24 hours, preferably 4-12 hours, and the calcination atmosphere is flowing air.
11. The preparation method according to claim 1, characterized in that: After high-temperature calcination, the catalyst prepared by spray drying has an attrition index of less than 1.0 wt% / h, preferably less than 0.50 wt% / h, and more preferably less than 0.30 wt% / h.
12. The preparation method according to claim 1, characterized in that: The average particle size of the catalyst prepared in step d) is 70-130 microns, preferably 80-100 microns.
13. The preparation method according to claim 1, characterized in that: In the catalyst prepared in step d), the content of TiO2 calculated as Ti is 0.500%-1.500% based on the weight of the catalyst.
Citation Information
Patent Citations
Titanium modified SAPO-34 molecular sieve and preparation method and application thereof
CN101898768A
Method for preparing formed molecular sieve catalyst, and product obtained by method and application thereof
CN101940944A
Fluidized bed catalyst and its preparation method
CN102371167A
Preparation method of molecular sieve fluidized bed catalyst
CN103736520A
Preparation method and application of microsphere catalyst for preparation of low-carbon olefin from methanol, ethanol or dimethyl ether
CN110270369A